2005
DOI: 10.1007/978-3-540-26643-3_8
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide and Methane Emissions from Estuaries

Abstract: Carbon dioxide and methane emissions from estuaries are reviewed in relation with biogeochemical processes and carbon cycling. In estuaries, carbon dioxide and methane emissions show a large spatial and temporal variability, which results from a complex interaction of river carbon inputs, sedimentation and resuspension processes, microbial processes in waters and sediments, tidal exchanges with marshes and flats and gas exchange with the atmosphere. The net mineralization of land-and marsh-derived organic carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 77 publications
5
64
4
Order By: Relevance
“…Surface waters were always over-saturated in CH 4 with respect to equilibrium with the atmosphere, with CH 4 concentrations ranging from 34 nmol l -1 (i.e., 1496% of saturation) to 1004 nmol l -1 (i.e., 51843% of saturation). These CH 4 over-saturations are within the range reported for temperate and tropical estuarine environments ranging between *70 and 160000% (Bange et al 1994;Upstill-Goddard et al 2000;Middelburg et al 2002;Abril and Borges 2004;Bange 2006;Shalini et al 2006).…”
Section: Description Of Study Areasupporting
confidence: 82%
See 3 more Smart Citations
“…Surface waters were always over-saturated in CH 4 with respect to equilibrium with the atmosphere, with CH 4 concentrations ranging from 34 nmol l -1 (i.e., 1496% of saturation) to 1004 nmol l -1 (i.e., 51843% of saturation). These CH 4 over-saturations are within the range reported for temperate and tropical estuarine environments ranging between *70 and 160000% (Bange et al 1994;Upstill-Goddard et al 2000;Middelburg et al 2002;Abril and Borges 2004;Bange 2006;Shalini et al 2006).…”
Section: Description Of Study Areasupporting
confidence: 82%
“…The CH 4 oversaturation in estuarine waters is the result of a complex combination of sources, sinks and transport. In estuarine channels, net CH 4 inputs from the sediments to the water column and CH 4 production in the water column are generally low because oxic and suboxic respiration dominate (Abril and Borges 2004). Consequently, CH 4 in estuarine waters originates from two major sources: (1) rivers, which receive CH 4 from soils, groundwater, wetlands and floodplains on the watershed (De Angelis and Lilley 1987;Richey et al 1988) and (2) tidal wetlands and mud flats, which are generally vegetated and enriched in organic matter to support methanogenesis (Bartlett et al 1987;Chanton et al 1989;Kelley et al 1995;Middelburg et al 2002;Abril and Borges 2004).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it was not until the late 1990s that a regional synthesis of fluxes of CO 2 out of the estuaries was made available by Frankignoulle et al (1998), who reported that CO 2 emissions from inner estuaries in Europe (average 50 mol m −2 yr −1 ) was a significant term in the regional CO 2 budget, equivalent to 5-10% of the total anthropogenic CO 2 emissions from western Europe. The first compilation of global inner estuarine fluxes of CO 2 was that of Abril and Borges (2004) and was based on only a handful of data. The datasets (Borges 2005;Borges et al 2005) grew gradually, and in 2009 an assessment including 32 estuaries was published (Chen and Borges 2009).…”
Section: Co 2 Degassing Flux In Inner Estuariesmentioning
confidence: 99%